(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Cytological examination of body fluids is a simple, minimally invasive, rapid, and cost-effective diagnostic tool widely used in the evaluation of malignant and non-malignant effusions. Pleural fluid, ascitic fluid, and cerebrospinal fluid (CSF) cytology play an important role in identifying metastatic malignancies and primary neoplastic involvement. Aim: To evaluate the cytological findings of pleural, ascitic, and cerebrospinal fluids in the detection of malignancy and to assess the diagnostic utility of body fluid cytology. Materials and Methods: This prospective observational study was conducted in the Department of Pathology, Naraina Medical College and Research Centre, Kanpur, Uttar Pradesh, India, over a period of one year. A total of 180 body fluid samples including pleural fluid, ascitic fluid, and CSF were analyzed. Samples were processed using conventional centrifugation and smear preparation techniques followed by staining with May-Grünwald-Giemsa (MGG) and Papanicolaou stains. Cytological findings were categorized as benign, suspicious, or malignant. Statistical analysis was performed using SPSS version 25. Results: Among 180 body fluid samples, pleural fluid constituted the majority of specimens followed by ascitic fluid and CSF. Malignant cells were detected in 38 cases (21.1%). Pleural effusions showed the highest rate of malignancy detection. Adenocarcinoma was the most common malignant cytological pattern identified. Reactive mesothelial proliferation was the most frequent benign finding. Conclusion: Body fluid cytology remains an effective, economical, and minimally invasive diagnostic modality for malignancy detection. Pleural fluid cytology demonstrated the highest diagnostic yield among the studied fluids. Early cytological evaluation significantly contributes to patient diagnosis, staging, and therapeutic management.